PERGESERAN NILAI DALAM KEHIDUPAN SOSIAL BUDAYA DAN PENDIDIKAN - Muh. Yusuf; Saprin; Syarifuddin Ondeng (CV. ADIBA AISHA AMIRA, 2025)
The shift in values in social, cultural, and educational life is a phenomenon that has become the focus of attention in modern society. This article examines the significant changes in values that lead to cultural and educational transformation. The study uses a descriptive-analytical approach to describe the impact of value shifts in diflerent contexts. In social life, the shift in values is reflected in changes in the attitudes and behavior of society related to norms, ethics, and morality. Globalization, increasingly sophisticated technology, and communication have aflected how values are adopted and interpreted by individuals and groups. These changes can create imbalances in social relationships, create conflicts of values, and change the dynamics of interpersonal interactions. In a cultural context, the shift in values also aflects the identity and tradition of a group. Traditional values often compete with more individualistic and consumerist modern values. It could threaten the sustainability of local cultures and stimulate the search for new identities that reflect changes in the patterns of society's values. In education, value shifts have a significant impact on curricula, teaching methods, and educational goals. Modern education tends to emphasize technical capabilities and global understanding, while moral and character aspects are often overlooked. This can lead to a generation that may have extensive knowledge, but a lack of strong values. Therefore, the shift in values in social, cultural, and educational life poses a serious challenge inining valuable values within societies. Intelligent change eflorts in curriculum development, the promotion of positive values, and intercultural dialogue can help overcome conflicts of values and promote better understanding between diflerent generations. Awareness of this shift in values is vital to ensuring that societies can maintain valuable cultural and educational sustainability in the face of changing times.